Systematic Review: "The Effectiveness of Counseling Strategies on Contraceptive Use in Women of Childbearing Age" - Filla Alfazriani Darsono; Nely Bonita (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
AbstractFamily Planning (KB) counseling is a key intervention to increase the use of contraceptives in women of childbearing age (WUS, aged 15-49 years), in order to reduce unplanned pregnancies and improve reproductive health. Various counseling strategies have been implemented, but their effectiveness varies based on the individual, social, and health care system contexts.  This systematic review aims to identify the effectiveness of family planning counseling strategies on the use of contraceptives in women of childbearing age. Evaluation of the Systematic Review using the PRISMA checklist with the framework (Women of reproductive age) AND (Contraceptive counseling) AND (countraceptive use). To determine the selection of studies that have been found. The protocol used in this study is JBI (Joanna Briggs Institute).Article search using 5 databases namely PubMed, Wiley, Sciencedirect, Reserch Rabbit, Cochrane. Insertion Criteria : The criteria included in this study are Indonesian or English articles with the last 5 years of publication and articles that discuss contraceptive counseling. Out of 452 articles, 10 articles were found to be likely to be relevant and meet the inclusion criteria. The results of the synthesis show that interpersonal, media-based, couple-counseling, and digital-based counseling strategies significantly improve knowledge, attitudes, and adherence to contraceptive use. Counseling that is carried out on a recurring and needs-based basis is also more effective in encouraging the selection of long-term contraceptive methods (MKJP). Structured and responsive counseling strategies have been shown to be effective in increasing contraceptive use in women of childbearing age. It is necessary to strengthen the capacity of health workers and innovate counseling media so that interventions become more adaptive and reach a wider population.